A computational simulation of rotor-fuselage flow interaction in hovering and forward flight - Ismail, Mohamad Hafiz (2007)
A helicopter rotor-fuselage flow interaction has been studied theoretically and numerically. The study began with the analysis of the induced velocity by helicopter rotor both in hovering and forward flight by using Momentum Theory, Blade Element Theory and Blade Element Momentum Theory. Three-dimensional steady and unsteady simulations of rotor-fuselage flow interaction have been conducted using Computational Fluid Dynamics (CFD) commercial software FLUENT 6.2 on ROBIN and AS355 helicopter. The study on ROBIN is to justify the method used in CFD simulation for this current research on AS355 is correct. The study emphasizes on flow generated during hovering and forward flight onto the helicopter fuselage. Aerodynamic forces on the fuselage have been obtained through theoretical analysis and numerical simulation. The Spalart-Allmaras turbulent model has been utilized to model the physics of flow related to the helicopter fuselage. This model is chosen in terms of its reliability, practical and proven to be effective in modeling the rotorfuselage flow interaction. The simulation was first carried out in steady state using Moving Reference Frame capability in FLUENT 6.2. this is then followed by unsteady simulation using Sliding Mesh Model, which is a time accurate simulation. Unsteady simulation was carried out because the nature of rotor-fuselage flow characteristic that is unsteady and periodic with time along azimuth angle. From this research it is found that the flow on the helicopter fuselage can be divided into two parts, which is a complex unsteady aerodynamic interaction that occur during hovering and low advance ratio, and a steady aerodynamic condition that occur at high advance ratio. At high advance ratio the rotor wakes flows above the body and only interacts with the fuselage pylon, and at this point the flow field of the helicopter fuselage is dominated by free stream velocity. A fully three dimensional and an unsteady computational method using Sliding Mesh Model has successfully model the rotor-fuselage flow interaction in AS355, a 5-seater helicopter. These results however provide preliminary understanding for designing the fuselage for optimal aerodynamic characteristics.